Targeting the immune system for the future of HIV therapy. (November 2007) - Landay, Alan
Alan Landay is Professor and Chairman of the Department of Immunology/Microbiology at Rush University Medical Center in Chicago (IL, USA). He has been involved in HIV research for over 20  years, having performed some of the first immune evaluations of HIV-infected hemophiliacs in 1982 while completing a postdoctoral fellowship at the University of Alabama, Birmingham (AL, USA). Dr  Landay joined the faculty at Rush University Medical Center in 1983 and helped establish the HIV research program, which has grown to encompass both a basic and clinical focus on immune studies in HIV. Dr  Landay served as Chair of the National Committee of Clinical Laboratory Standards Committee on Flow Cytometry, which produced the first national standard on CD4 testing. He has also served as an advisor to the College of American Pathologists, NIH and WHO on Standardization of CD4 Testing. Dr  Landay''s current research focus is on immune pathogenesis and immune-based therapy of HIV disease. He is past Chair of the Immunology Research Agenda Committee of the AIDS Clinical Trial Group NIH Program and he has served on the Executive Committee of the Forum for HIV Collaborative Research. Dr  Landay is Chair of the Office of AIDS Research Panel on Pathogenesis. He serves on NIH, AmFar and State of California grant review panels. He has served as a mentor for over 15  graduate students and postdoctoral fellows who have gone on to obtain academic positions. Dr  Landay has published over 200  papers focused on basic and clinical studies of HIV. Here, he talks to Head of Commissioning, Laura Dormer, about his current and future research.